Pengembangan E-Modul Menggunakan Aplikasi Book Creator Berbasis Pendekatan Saintifik dan Keterampilan Berpikir Kreatif Pada Pembelajaran IPA Siswa Kelas IV SD - Larasati, Sekar Reviyana; Rukmana, Diki (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The purpose of this study was to develop an interactive e-module that combines a scientific approach and creative thinking skills in learning science for grade IV SD. The development method used is the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Science education experts and teachers are involved in the validation process to ensure the validity of the content and design of the e-module. The results of the study show that the developed e-module has content that is in accordance with the science curriculum for grade IV SD and has been integrated with a scientific approach and creative thinking skills. This e-modul uses the Book Creator application which allows students to interact with learning materials through images, text, videos, and other interactive elements. In addition, the e-module also contains tasks that encourage students to use creative thinking skills in solving scientific problems. The use of this e-module is expected to increase students interest in learning, as well as strengthen understanding of scientific concepts and creative thinking skills in science learning. The development of e-modules using the Book Creator application based on a scientific approach and creative thinking skills in science learning for class IV SD has great potential to improve the quality of learning and develop students' creativity in science. Keywords: E-Modul; Book Creator; Creative Thinking, Science